The Role of Advertising in Social Media on Holiday Destinations Choice Among the Millennial Travelers - Auliya, Anisatul (Jurnal Penelitian Pariwisata, 2020)
Social Media has a big influence in tourism industry, social media also played as a role in tourism marketing, It has a major effectiveness as a marketing tool and performs with multiple functions. The purpose of this study to discussing the importance of social media when choosing a holiday destinations for the millennial traveler. This paper was conducted in January - April 2020 using descriptive quantitative research methods. The data collection technique of this research is survey analysis. Primary data is collected by questionnaire. There were 72 questionnaires have been distributed according the number of active students at second semester from tourism study in Vocational Education Program, University of Indonesia academic year 2019/2020. After the questionnaires were completed, SPSS 25 version is used to analyze the data. According to the result of this study, social media has a big influences when choosing the holiday destination. Instagram and YouTube are the most important media social platform to get the information and building the trust about the tourism destination.